WHEN TRUST LEADS TO LOYALTY : A STUDY ON THE INDONESIAN SHARIA BANK IN ACEH - Yusniar, Yusniar; Bahri, Samsul (LPPM Universitas Malikussaleh, 2024)
In many ways, trust is seen as the basis for relationships with consumers. The importance of a sense of trust, will be as important as building the business itself. Hence, trust is one measure by which the business objectives can be further achieved. This research proposes and tests a model of brand trust that includes both its antecedents and its consequences. The model is rooted in a causal approach and features established brand trust constructs. This study was conducted by quantitative approeaches, the sampling technique used is non-probability sampling. The results show that BSI is considered a preferred brand and as such consumers appear to be loyal and want to spread the word of mouth to another customer. Futhermore, the leader need to consider this antecedent as a strategy to maintain customer loyalty in the future